Some Lexical Collocational Patterns in Late Middle English Legal Texts - Iglesias-Rábade, Luis (Miscelánea: A Journal of English and American Studies, 2007)
The purpose of this study is to attempt to scrutinize the weight of collocations in legal late Middle English, and to show how they either specialized in this technical area or slipped into common speech. My analysis of the collocational framework in late Middle English legal texts tries to follow a lexical description based on the analysis of ‘collocation’ and ‘set’ as counterparts of ‘structure’ and ‘system’ in grammatical analysis, emphasizing the collocational structure rather than the rules that operate within the set. Two corpora were designed: a non-Technical Corpus was drafted from a body of non-technical English texts of late Middle English which has been activated as a corpus of reference. In like manner, a minor body of the legal texts of the same period has been built to compare it with the reference corpus. Wordsmith Tools have been used to draft word lists and keyword lists of the two corpora. Collocations have been retrieved and filtered out applying Church and Hanks’s Mutual Information. The most important conclusion is that most of the collocational types detected in the legal corpus in the six categories covered by this study hardly occur in the common corpus.